PENDAMPINGAN BUDIDAYA PEPAYA CALINA UNTUK PENINGKATAN PENGETAHUAN DAN KETERAMPILAN MASYARAKAT RT BELAR DESA SUKADANA, KECAMATAN PUJUT, KABUPATEN LOMBOK TENGAH - Aluh Nikmatullah; Herman Suheri; Dwi Noorma Putri; Nihla Farida; Liana Suryaningsih B (Universitas Mataram, 2026)
Sukadana Village, one of the buffer zones of the Mandalika Special Economic Zone (SEZ), possesses agroclimatic potential that supports horticultural cultivation, including Calina papaya, which is highly valued for its nutritional and economic benefits. Calina papaya is small in size, has thick flesh, a consistently sweet taste, and a long shelf life. It is commonly served in hotels, restaurants, and catering services. However, residents of RT Belar have not widely cultivated this commodity due to limited knowledge and technical skills. This Community Service Program (PKM) aimed to enhance the knowledge and skills of residents in RT Belar regarding Calina papaya cultivation. The program was implemented for 5 months from Mey to September 2025, using participatory and contextual approaches. The PKM activities included Initial outreach, trainings and supervision on Calina papaya cultivation including home garden optimization, seedling preparation, planting, crop maintenance, pest and disease control, and post-harvest handling. The activities were followed by evaluation using a Likert Scale. Evaluation results showed an improvement in participants’ knowledge (from an average score of 2.79 to 3.22) and skills (from 2.64 to 3.62), particularly in seedling and crop maintenance techniques. The program’s success was supported by the community’s open and welcoming culture, the use of appropriate methods combining technical training and field mentoring, and the duration of engagement that fostered trust and strong relationships between facilitators and participants. For sustainability, Calina papaya cultivation should be further developed through strengthened local institutions and integration into the community’s socio-economic systems. This PKM was successfully implemented and has enhanced the community’s knowledge and skills while simultaneously promoting the economic and nutritional potential of Calina papaya cultivation.